A virtual roundtable on Iser’s legacy Part IV: a conversation with Federico Bertoni (ENTHYMEMA, 2017)
In this article you find the fourth and last part of our ‘virtual roundtable’ on Wolfgang Iser’s legacy with Gerald Prince, Mark Fremman, Marco Caracciolo and Federico Bertoni. In part IV we discuss with Federico Bertoni the state of theories of reading and the centality of Iser’s work in the field, the ethical potential of literature, and the role of literary criticism and theory today.
Keywords: Iser; reader’s response; literary theory; ethics; aesthetic reception